Wielowymiarowa analiza porównawcza wybranych giełd papierów wartościowych na świecie - Koralun-Bereźnicka, Julia (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper aims at evaluating the effects of the international capital markets integration through identifying the similarities between 44 world stock exchanges. The comparison was based on a set of 56 variables constituting yearly indicators from the end of 2005 which were categorized into three groups: variables describing equity markets, bonds' markets and general stock performance indices. The application of the multivariate analytical methods, such as cluster analysis or k-means clustering, revealed two major clusters of stock exchanges with different level of development. The content of the identified clusters does not fully correspond with geographical regions of the stock exchanges. This could prove progressing convergence process, which gradually reduces the country or region effect as a performance factor of capital markets. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 174-184